Comparative Analysis of Rhizosphere Fungi in Ageratina Adenophora and Associated Native Species in Far-Western Nepal - Binadi, Dinesh; Jha, Sanjay Kumar; Pant, Ramesh Raj; Thapa, Lal B. (Tribhuvan University Journal, 2023)
Root exudates play a significant role in influencing the rhizosphere microbes. Fungi are an important group of microbes that are influenced by plant root exudates. As invasive alien plant species secretes several allelochemicals and impact soil microbes, this study compared the fungal community in one of the invasive weeds Ageratina adenophora with native species (Rubus ellipticus, Shorea robusta and Imperata cylindrica) in far-western Nepal. The rhizosphere soil was sampled by uprooting respective plants, and the soils were cultured using Czapek Dox Agar and PDA media. A total of 49 fungal species were identified from the plant rhizospheres. A. adenophora altered the species richness, occurrence and frequency of fungi in soil. The pathogenic fungi Aspergillus niger, Myrothecium sp., Phoma sp., Rhizoctonia sp., Pythium oligandrum, Verticillium spp. were the most frequently occurring rhizosphere fungi in all plants and they showed their host specificity in the rhzosphere. The fungi species such as Paecilomyces lilacinus, Aspergillus flavus, Myrothecium sp., Penicillium citrinum, P. chrysogenum, Rhizoctonia sp., Mucor circinelloides, Hypocrea sp., Trichoderma hypoxylon, T. sparsum, Gliocladium sp., Hypomyces sp., Aspergillus niger and M. circinelloides were common in all native plants. Even minor variations in the physicochemical properties of soil can change the presence of fungal species in the root zone, as indicated by the analysis of soil chemicals.